Intraoperative Label‐Free Photoacoustic Histopathology of Clinical Specimens (Laser Photonics Rev. 15(10)/2021). Issue 10 (18th October 2021) - Baik, Jin Woo; Kim, Hyojin; Son, Myeongjoo; Choi, Junwon; Kim, Kwang Gi; Baek, Jeong Heum; Park, Yeon Ho; An, Jungsuk; Choi, Hae Young; Ryu, Seon Young; Kim, Jin Young; Byun, Kyunghee; et al.
Abstract : Photoacoustic Histopathology As described in article number 2100124 by Jin Young Kim, Kyunghee Byun, Chulhong Kim, and co‐workers, label‐free Intraoperative histopathology can be performed photoacoustically on clinical specimens without complex procedures (freezing, sectioning, and staining) by steering UV light and generated ultrasound simultaneously using a high‐speed waterproof microelectromechanical systems (MEMS) scanner, which has the capability to provide not only histoarchitectural features but also cytologic features for guiding pathologists.